SCIENTIFIC CONCEPTION OF STATISTICAL METHODOLOGY: METHODS, INDEXES, CRITERIA OF RELIABILITY - Опря, А. Т. (Scientific Progress & Innovations, 2013)
Conceptual approaches of statistical methodology are considered in research of intercommunications of the economic phenomena and processes. The necessity of application of statistical methods is grounded for deep research of causalinvestigation connections from positions of approach of the systems of their use: methods, statistical indexes, estimations of reliability. An attempt to unite the empiric aspect of research work with scientific methodology is done, coming from conceptual positions of statistical science.